The Importance of Financial Literacy Among Elementary School Students: A Case Study of Savings Activities in Menur Pumpungan State Elementary School Surabaya - Mansur, Abi; Lestari, Gunarti Dwi; Nugroho, Rivo (IKIP Widya Darma Surabaya, 2024)
Objective: This study aims to investigate the importance of financial literacy among elementary school students and assess the efficacy of savings programs in promoting financial education. Method: Utilizing a qualitative case study approach, data were gathered through observations, interviews, and document analysis. The study focused on a collaborative initiative between elementary schools and Bank Jatim to implement savings activities. Participants included students, teachers, and bank representatives. Results: The findings highlight the significance of financial literacy in elementary education, emphasizing its role in fostering financial management skills and responsible decision-making among students. The savings programs facilitated by Bank Jatim demonstrated a positive impact on students' financial knowledge, behavior, and attitudes. Through regular savings activities, students developed habits of diligence, discipline, independence, and patience. Additionally, the collaboration between schools and the bank provided a practical platform for financial learning, helping students distinguish between wants and needs and relieving financial burdens on parents. Novelty: This research contributes to the literature by providing empirical evidence of the effectiveness of school-based savings programs in enhancing financial literacy among elementary students. By employing a qualitative case study approach, the study offers insights into the implementation and outcomes of such initiatives, highlighting their potential to instill lifelong financial skills and positively impact students' financial well-being.